Hierarchical-Reflective Learning Strategy in Santri Mentorship: Analyzing the Tiered Leadership Model as Pedagogical Technology in the Dormitory of Pondok Modern Darussalam Gontor - Muhammad Yusuf Mustaqim; Unifah Rosyidi; Muhammad Takdir; Syafaat Ariful Huda; Rifaldi Nurul Akbar (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
This study analyzes the tiered leadership model in the dormitory of Pondok Modern Darussalam Gontor (PMDG) as a hierarchical-reflective learning strategy for santri mentorship. Employing a qualitative descriptive case study design, the research collected data through in-depth interviews, participant observation, and document analysis involving 18 key informants across stakeholder groups. The findings reveal that the system functions as an integrated pedagogical technology, synergizing a structured hierarchical scaffold, a cyclic experiential-reflective engine (POAC/muhasabah), and a foundation of Islamic values. This integration transforms the dormitory into a dynamic learning laboratory, where santri progressively develop leadership competencies through authentic practice grounded in ethical reflection. The model effectively bridges theoretical leadership education with moral character formation, cultivating disciplined, autonomous, and service-oriented leaders. The study concludes that the PMDG model presents a replicable framework for value-based leadership pedagogy. Future research should employ longitudinal and comparative designs to further validate its long-term outcomes and explore potential integrations with digital technologies without compromising its relational and reflective core.